2006
DOI: 10.1590/s1519-566x2006000600015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parasitism by Chelonus insularis Cresson (Hymenoptera: Braconidae) on the susceptibility of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) to insecticides

Abstract: Neotropical Entomology 35(6):818-822 (2006) Infl uencia del Parasitismo por Chelonus insularis Cresson (Hymenoptera: Braconidae) sobre la Susceptibilidad de Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) a Insecticidas RESUMEN -El parasitoide huevo-larva Chelonus insularis Cresson es un parasitoide clave del cogollero del maíz, Spodoptera frugiperda (J.E. Smith) durante la segunda generación de campo en el Valle Superior del Río Magdalena de Colombia. A pesar de la presión de selección se encue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…Adults of the larval parasitoid Cotesia flavipes (Cameron) exposed to residues of synthetic insecticides and fed on contaminated sugary solutions suffered varying degrees of mortality, with organophosphates and carbamates being the most toxic (Akhtar et al 2021). Zenner et al (2006) showed that FAW larvae are more susceptible to chlorpyriphos, methomyl and cypermethrin when parasitized by the egg-larval FAW parasitoid Chelonus insularis. This hints that insecticide exposure through FAW larvae may reduce the chance of successful parasitoid development, even at low pesticide concentrations.…”
Section: Non-target Effects Of Insecticide Use Towardmentioning
confidence: 99%
“…Adults of the larval parasitoid Cotesia flavipes (Cameron) exposed to residues of synthetic insecticides and fed on contaminated sugary solutions suffered varying degrees of mortality, with organophosphates and carbamates being the most toxic (Akhtar et al 2021). Zenner et al (2006) showed that FAW larvae are more susceptible to chlorpyriphos, methomyl and cypermethrin when parasitized by the egg-larval FAW parasitoid Chelonus insularis. This hints that insecticide exposure through FAW larvae may reduce the chance of successful parasitoid development, even at low pesticide concentrations.…”
Section: Non-target Effects Of Insecticide Use Towardmentioning
confidence: 99%
“…Many insecticides 291 are toxic to developing and adult C. marginiventris (Wilkinson et al, 1979;Atwood et 292 al., 1997;Tillman and Scott, 1997;Pietrantonio and Benedict, 1999;Tillman and 293 Mulrooney, 2000) and Ch. insularis wasps (Penagos et al, 2005;Zenner et al, 2006), 294 either through direct toxicity of the insecticides or due to death of the host. If 295 applications are not made directly to adult wasps, it appears that adult emergence from 296 parasitized larvae may not be affected by host larvae feeding on plant material previously 297 treated with insecticides (Atwood et al, 1998).…”
Section: Collection Of Larvae 95mentioning
confidence: 99%
“…La ausencia del efecto de una formulación comercial del Bacillus thuringiensis , la cual contenía las toxinas Cry1Aa, Cry1Ab, Cry1Ac, Cry2A y Cry2B (Lui & Tabashnik, 1997), sobre C. insularis fue encontrada por Zenner et al (2006); la sola presencia en el Bollgard del Cry1Ac, toxina que no controla satisfactoriamente a las larvas del S. frugiperda (Zenner de Polanía et al 2005), . 2005), .…”
Section: Algodónunclassified